Presencia de poblaciones leucocitarias en el útero de los rumiantes y sus posibles implicaciones en la reproducción bovina. Revisión de literatura (1999)
ABSTRACT: Under physiological conditions the mammal uterus is exposed to fetal and paternal antigens that could generate immune responses harmless toward the semiallogenic conceptus at any time during pregnancy. Several strategies evolved have evolved depending on the specie in order to maintain the fetus alive which includes: type of placentation, the presence of specific cell population at the materno-fetal interface, and specific cytokines produced at the local microenvironment during the pregnancy. The placentation in ruminants is characterized by the presence of some lineage of γδTCR lymphocytes which display specific protective functions similar to that excerpted by NK cell (LGL and GMG) in primates and rodents, respectively. These cells also have similar morphology to NK lineages, but exhibits different expression of specific cell surface markers. The proposal of the present article is to review leukocyte populations present at the ruminant uterus during the processes of implantation, placentation, pregnancy maintenance, and parturition. Thereafter, we focused on the cell surface markers until now characterized and the homologies between ruminants and human or murine uterine leukocyte populations. Finally we shall mention specific topics for development of research in bovine reproductive immunology with potential use for improving reproductive efficiency.